Corticosteroid Induced Hypokalemic Periodic Paralysis: A Case Report - Kaçan, Turgut; Baloğlu, Selen Kaçan; Çubukçuoğlu, Tarık (Fırat University, 2013)
Hypokalemic periodic paralysis (HPP) is a rare disease characterized by reversible attacks of muscle weakness due to hypokalemia. The attacks may occur everyday, weak, month or once a year and may last for a few hours to several days. The serum potassium level is low during the attack. However, the serum potassium levels are normal between two attacks. The most common causes of HPP are familial periodic paralysis (FPP), thyrotoxic periodic paralysis (TPP) and sporadic periodic paralysis (SPP). We report, hypokalemic periodic paralysis due to use of corticosteroid.

Hipokalemik periyodik paralizi (HPP), hipokaleminin neden olduğu kas güçsüzlüğü atakları ile karakterize geri dönüşümlü nadir bir hastalıktır. Ataklar günde, haftada veya yılda bir olup bir kaç saat veya bir kaç gün sürebilir. Atak sırasındaki serum potasyum seviyesi düşük iken ataklar arasındaki serum potasyum seviyeleri normaldir. En sık sebepleri, sırasıyla ailesel periyodik paralizi (APP), tirotoksik periyodik paralizi (TPP) ve sporadik periyodik paralizidir (SPP). Burada kortikosteroid kullanımına bağlı gelişen hipokalemik peryodik paralizi olgusu rapor edilmiştir.
Kortikosteroid ile İndüklenen Hipokalemik Periyodik Paralizi: Olgu sunumu